The influence of the BI Rate , Inflation and Rupiah - US Exchange Rate on stock price Sub Sector Banking (Case Study In Stock Price Sub Sector Banking years 2009-2013 ) - Antysa Chlara Norenz Nandya; Wahyu Hidayat; Saryadi Saryadi (Universitas Diponegoro, 2015)
Banking stocks are the biggest contributor to the existing capitalization on the stock exchanges in Indonesia. Banking stock price movements will be able to directly affect the performance of the Indonesian capital market because of large capitalization . The movement of stock prices are influenced by many factors , one of which is the macro economic factors. In relation to macroeconomic Indonesia, the bank acts as a control over the monetary policy issued by Bank Indonesia . Because of this, the study raised the BI rate, inflation, and Rupiah-US Exchange Rate as macroeconomic factors suspected to affect stock prices subsector banks. This study aims to determine the effect of the BI Rate , Inflation and Rupiah - US Exchange Rate against the banking sub-sector stock price years 2009-2013. Methods of data collection using secondary data of each variable . The sample in this study amounted to 13 banks with purposive sampling technique. Scale measurements using a measuring scale ratio. In linear regression analysis was used and the significance test using SPSS 15.0 . From the analysis of data it can be concluded that BI rate has no significant effect on stock prices of banking sub- sector . Inflation has no significant effect on stock prices of banking sub- sector . Rupiah -US exchange rate has no significant effect on stock prices of banking sub- sector. Simultaneously, BI Rate, Inflation and Rupiah - US Exchange Rate has a significant impact on stock prices of banking sub- sector amounted to 14.2 % . The advice can be given that investors consider also other factors in addition to the factors BI Rate, Inflation and Rupiah - US as a material consideration in decision making stock purchases, especially in the banking sub-sector stocks .